Evidence for Altered Ca2+ Handling in Growth Associated Protein 43-Knockout Skeletal Muscle - Caprara, Giusy A.; Morabito, Caterina; Perni, Stefano; Navarra, Riccardo; Guarnieri, Simone; Mariggiò, Maria A. (Frontiers in Physiology, 2016)
Neuronal growth-associated protein 43 (GAP43) has crucial roles in the nervous system, and during development, regeneration after injury, and learning and memory. GAP43 is expressed in mouse skeletal muscle fibers and satellite cells, with suggested its involvement in intracellular Ca2+ handling. However, the physiological role of GAP43 in muscle remains unknown. Using a GAP43-knockout (GAP43-/-) mouse, we have defined the role of GAP43 in skeletal muscle. GAP43-/- mice showed low survival beyond weaning, reduced adult body weight, decreased muscle strength, and changed myofiber ultrastructure, with no significant differences in the expression of markers of satellite cell and myotube progression through the myogenic program. Thus GAP43 expression is involved in timing of muscle maturation in-vivo. Intracellular Ca2+ measurements in-vitro in myotubes revealed GAP43 involvement in Ca2+ handling. In the absence of GAP43 expression, the spontaneous Ca2+ variations had greater amplitudes and higher frequency. In GAP43-/- myotubes, also the intracellular Ca2+ variations induced by the activation of dihydropyridine and ryanodine Ca2+ channels, resulted modified. These evidences suggested dysregulation of Ca2+ homeostasis. The emerging hypothesis indicates that GAP43 interacts with calmodulin to indirectly modulate the activities of dihydropyridine and ryanodine Ca2+ channels. This thus influences intracellular Ca2+ dynamics and its related intracellular patterns, from functional excitation-contraction coupling, to cell metabolism, and gene expression.